Effect of chronic ethanol consumption in rhesus macaques on the nucleus accumbens core transcriptome. (4th May 2021) - Walter, Nicole; Cervera‐Juanes, Rita; Zheng, Christina; Darakjian, Priscila; Lockwood, Denesa; Cuzon‐Carlson, Verginia; Ray, Karina; Fei, Suzanne; Conrad, Don; Searles, Robert; Grant, Kathleen; Hitzemann, Robert
Abstract: The nucleus accumbens core (NAcc) has been repeatedly demonstrated to be a key component of the circuitry associated with excessive ethanol consumption. Previous studies have illustrated that in a nonhuman primate (NHP) model of chronic ethanol consumption, there is significant epigenetic remodeling of the NAcc. In the current study, RNA‐Seq was used to examine genome‐wide gene expression in eight each of control, low/binge (LD*), and high/very high (HD*) rhesus macaque drinkers. Using an FDR < 0.05, zero genes were significantly differentially expressed (DE) between LD* and controls, six genes between HD* and LD*, and 734 genes between HD* and controls. Focusing on HD* versus control DE genes, the upregulated genes ( N  = 366) were enriched in genes with annotations associated with signal recognition particle (SRP)‐dependent co‐translational protein targeting to membrane (FDR < 3 × 10 −59 ), structural constituent of ribosome (FDR < 3 × 10 −47 ), and ribosomal subunit (FDR < 5 × 10 −48 ). Downregulated genes ( N  = 363) were enriched in annotations associated with behavior (FDR < 2 × 10 −4 ), membrane organization (FDR < 1 × 10 −4 ), inorganic cation transmembrane transporter activity (FDR < 2 × 10 −3 ), synapse part (FDR < 4 × 10 −10 ), glutamatergic synapse (FDR < 1 × 10 −6 ), and GABAergic synapse (FDR < 6 × 10 −4 ). Ingenuity Pathway Analysis (IPA) revealed that EIF2 signaling and mTOR pathways were significantly upregulated in HD* animals (FDR < 3 × 10 −33 and <2 × 10 −16, respectively). Overall, the data supported our working hypothesis; excessive consumption would be associated with transcriptional differences in GABA/glutamate‐related genes. Abstract : The nucleus accumbens core has been demonstrated to be a key component of the circuitry associated with excessive ethanol consumption; previous work has shown that this brain region exhibits epigenetic modeling in nonhuman primates. In the current study, RNA‐Seq was used to examine genome‐wide gene expression in eight rhesus macaque ethanol drinkers. Overall, the data showed that excessive consumption would be associated with transcriptional differences in GABA/glutamate‐related genes.